2003
DOI: 10.1002/ejic.200300146
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Prototropic Exchange Rate at the Water Molecule Coordinated to a GdIII Ion

Abstract: The aim of this work is to assess whether it is possible to control the rate of the prototropic exchange in a class of DTPA bis-amide Gd III complexes.In the last decade much attention has been devoted to the understanding of the determinants of the water-exchange process in Gd III complexes because their successful application as MRI contrast agents is related to the occurrence of a suitable exchange lifetime (τ M ) of the coordinated water.[1Ϫ4] The latter parameter inversely affects the innersphere relaxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…These values are similar to those reported for Gd 3 + complexes of other DTPA-bisamides. [38,39] The pH dependence of the relaxivities of the complexes increases signficantly at low and high pH values (Figure 1). At pH < 2 both complexes show a steep increase in relaxivity to about 13 s À1 mm…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…These values are similar to those reported for Gd 3 + complexes of other DTPA-bisamides. [38,39] The pH dependence of the relaxivities of the complexes increases signficantly at low and high pH values (Figure 1). At pH < 2 both complexes show a steep increase in relaxivity to about 13 s À1 mm…”
mentioning
confidence: 94%
“…It has been reported that the prototropic exchange rate is modulated by the overall charge of the complex under basic conditions; exchange is faster for positively charged and slower for negatively charged complexes. [39] This effect has been explained in terms of the ease of access of OH À ions to the coordinated water molecule. It is likely that the activation of prototropic exchange plays a role in the relaxivity enhancement observed for the two complexes GdL 1 and GdL 2 under basic conditions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Aime and coworkers have recently been able to modulate the prototropic exchange rate of the coordinated water molecules of several Gd DTPA-BMA analogues by changing the overall charge of the complex. 20 Similarly, Sherry and coworkers have shown that although the lanthanide coordination geometry of their Eu-DOTA analogues does play a role in determining τ M , the identity of the ligand side chains, and particularly the charge and polarity they induce in the complex, can also have a determining effect. 21 .…”
Section: Introductionmentioning
confidence: 99%